1994
DOI: 10.1007/bf01870932
|View full text |Cite
|
Sign up to set email alerts
|

Epidural fentanyl and sufentanil for intra- and postoperative analgesia

Abstract: In a double-blind, randomized study the efficacies of concentrated fentanyl and sufentanil injections as intraoperative epidural analgesics were compared. Also, the equivalent dose of fentanyl and sufentanil administered by continuous infusion during the first 24 h postoperatively, expressed in analgesia and also considering the side-effects was determined. 53 Patients undergoing elective thoracotomy, aortic surgery and bowel surgery were randomized and treated double-blind with fentanyl 0.250 mg/ml or sufenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Despite the sufentanil induced release of histamine from basophils, the nature of post-opioid pruritus does not appear to be directly related to this phenomenon; naloxone has been reported to cause the gradual subsidence of post-opioid pruritus, but at a much slower rate than other side effects3,14,17). Previous comparative studies on the incidence of pruritus after fentanyl or sufentanil via IV or epidural PCA found no significant difference between the two drugs6,9,16,23). Headache and hypotension occurred in 1 case each in their study groups (4.8%).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Despite the sufentanil induced release of histamine from basophils, the nature of post-opioid pruritus does not appear to be directly related to this phenomenon; naloxone has been reported to cause the gradual subsidence of post-opioid pruritus, but at a much slower rate than other side effects3,14,17). Previous comparative studies on the incidence of pruritus after fentanyl or sufentanil via IV or epidural PCA found no significant difference between the two drugs6,9,16,23). Headache and hypotension occurred in 1 case each in their study groups (4.8%).…”
Section: Discussionmentioning
confidence: 75%
“…Some studies have reported sufentanil has a lower tendency than fentanyl to induce nausea and vomiting9,12,17,23). whereas other have reported it has a greater tendency6,16).…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil is proven to be more potent than fentanyl with less sedation. [5] Potency ratio of sufentanil/fentanyl has been reported to be 5-7:1 for intravenous administration, but we cannot extrapolate this data in case of epidural route. As lipid solubility of sufentanil id=s higher in case of intravenous route this will result into higher penetration of BBB resulting into higher ratio, while in case of epidural route, higher lipid solubility results into larger uptake of it into epidural fat, which ultimately results into decreased potency ratio in comparison to intravenous route.…”
Section: Introductionmentioning
confidence: 80%
“…Opioids like fentanyl and sufentanil have been successfully used for postoperative analgesia by epidural route. [2][3][4][5] Advantages includes avoidance of systemic toxicity, easy supplementation by catheter, early mobilization and low failure rate. Opioids since their first use in the epidural and subarachnoid space, have become the mainstay of postoperative pain relief.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation